Two new species and taxonomic notes on the Neotropical spiny orb-weaving spi-ders Micrathena and Chaetacis (Araneae: Araneidae), with remarks on the development of Micrathena excavata IVAN L. F. MAGALHÃES & ADALBERTO J. SANTOS (Brazil) - Magalhães, Ivan L. F.; Santos, Adalberto J. (Zootaxa, 2011)
In this paper, M. yanomami n. sp., from Brazilian Amazonia, Chaetacis bandeirante n. sp., from Central Brazil, and the males of M. gaujoni Simon, 1897 and M. ruschii (Mello-Leitão, 1945) n. comb. , respectively from Ecuador and Brazil, are described and illustrated for the first time. An ontogenetic series of the last development stages of both sexes of Micrathena excavata (C. L. Koch, 1836) is illustrated and briefly described. Adult females are larger and have longer legs and larger abdomens than adult males. Probably females undergo at least one additional moult before adulthood, compared to males. Micrathena ornata Mello-Leitão, 1932 is considered a junior synonym of M. plana (C. L. Koch, 1836), and M. mastonota Mello-Leitão 1940 is synonymized with M. horrida (Taczanowski, 1873). Acrosoma ruschii Mello-Leitão, 1945 is revalidated, transferred to Micrathena and considered a senior synonym of M. cicuta Gonzaga & Santos, 2004. Chaetacis necopinata (Chickering, 1960) is recorded for Brazil for the first time. Chaetacis incisa (Walckenaer, 1841) is considered a nomen dubium.